The Impact of the Use of the Program (FIFA11+S) in the Kinetic Capabilities and the Prevention of Injuries of Elite Handball Players’ Shoulder Joint - Jasim, Alaa Mohammed; Shehab, Rusul.Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
Handball is one of the collective games which increased its popularity throughout the world, especially in Europe, characterized by the speed and strength of public excitement and consequently become the focus of attention of many researchers and workers in the field of sports medicine and rehabilitation of sports injuries, and have the game on many of the repetitive movements, including the movements of the corrigendum scrollbars. The experimental approach was used with a group of tribal conference test the research problem. The use of FIFA 11+S program was effective in developing the capabilities of mobility of the shoulder and the attention of the special capabilities of the top party can be the result of a detailed prevention comes good shoulder which affect and gives positive results in performance, the skills of the corrigendum scrollbars handball researchers therefore recommends using preventive programs training courses contribute to the proper exercise intensity gradient applied such as FIFA 11+S program in the Training Unit through the development of physical side Al-mahari performance-related pay more attention to prevention programs, which help to protect the players during the training or contests.